Effects of Interface Damage Resulting from the Separation of Layered Strata on Bolt Anchoring Systems - Xiaowei Feng; Nong Zhang; Chuangxin Lv (Shock and Vibration)
Layered strata occurrence is frequently seen in underground constructions, the man-made excavation is thus easy to cause separation between neighboring strata. The sudden and unexpected occurrence of separation will induce significant shock wave and vibration to relative bolting system that initially holds the normal working space for underground production. The bolting system is extremely sensitive to this shock and is easily weakened or damaged. By examining the locations of strata separation and the extent of damage along an anchoring interface, this paper investigates the factors that influence the support strength of anchoring system. The results show that the support strength of a bolt is independent of the separation location if the resin-rock interface is intact. The opposite is the case if the separation width between the neighboring strata exceeds the ultimate critical value, which induces damage along the interface. In this case, the support strength increases exponentially as the separation increases. Separation at the free loading end dramatically decreases the support strength. However, this decrease is mitigated if the separation is located in the middle of the anchoring body or at the loading end. These results are then calibrated and verified in a laboratory test.